Regioselective Ring‐Opening of Glycidol to Monoalkyl Glyceryl Ethers Promoted by an [OSSO]‐FeIII Triflate Complex. Issue 15 (17th July 2019) - Monica, Francesco Della; Ricciardi, Maria; Proto, Antonio; Cucciniello, Raffaele; Capacchione, Carmine
Abstract: A Fe III ‐triflate complex, bearing a bis‐thioether‐di‐phenolate [OSSO]‐type ligand, was discovered to promote the ring‐opening of glycidol with alcohols under mild reaction conditions (0.05 mol % catalyst and 80 °C). The reaction proceeded with high activity (initial turnover frequency of 1680 h −1 for EtOH) and selectivity (>95 %) toward the formation of twelve monoalkyl glyceryl ethers (MAGEs) in a regioselective fashion (84–96 % yield of the non‐symmetric regioisomer). This synthetic approach allows the conversion of a glycerol‐derived platform molecule (i.e., glycidol) to high‐value‐added products by using an Earth‐crust abundant metal‐based catalyst. Abstract : The use of an Earth‐crust abundant metal‐based catalyst is proposed for the regioselective production of monoalkyl glyceryl ethers through ring‐opening of glycidol with alcohols under mild reaction conditions.